Neuromuscular aspects of sport performance (The encyclopaedia of sports medicine, XVII, 2011)
This new title in the Encyclopaedia of Sports Medicine Series from the Medical Commission of the International Olympic Committee presents in one volume the latest information on neuromuscular function…